Processing of the FMRFamide precursor protein in the snail Lymnaea stagnalis: characterization and neuronal localization of a novel peptide, 'SEEPLY' - Santama, N; Li, K W; Bright, K E; Yeoman, M; Geraerts, W P; Benjamin, P R; Burke, J F (The European journal of neuroscience, 1993)
In the pulmonate snail Lymnaea stagnalis, FMRFamide-like neuropeptides are encoded by a multi-exon genomic locus which is subject to regulation at the level of mRNA splicing. We aim to understand the post-translational processing of one resulting protein precursor encoding the tetrapeptide FMRFamide and a number of other putative peptides, and determine the distribution of the final peptide products in the central nervous system (CNS) and periphery of Lymnaea. We focused on two previously unknown peptide sequences predicted by molecular cloning to be encoded in the tetrapeptide protein precursor consecutively, separated by the tetrabasic cleavage site RKRR. Here we report the isolation and structural characterization of a novel non-FMRFamide-like peptide, the 22 amino acid peptide SEQPDVDDYLRDVVLQSEEPLY. The novel peptide is colocalized with FMRFamide in the CNS in a number of identified neuronal systems and their peripheral motor targets, as determined by in situ hybridization and immunocytochemistry. Its detection in heart excitatory motoneurons and in nerve fibres of the heart indicated that the novel peptide may play a role, together with FMRFamide, in heart regulation in the snail. The second predicted peptide, STEAGGQSEEMTHRTA (16 amino acids), was at very low abundance in the CNS and was only occasionally detected. Our current findings, suggestive of a distinct pattern of post-translational processing, allowed the reassessment of a previously proposed hypothesis that the two equivalent sequences in the Aplysia FMRFamide gene constitute a molluscan homologue of vertebrate corticotrophin releasing factor-like peptides.